Economic Evaluation For Oil and Gas Exploration Drilling Project - Wiryono, Sudarso Kaderi; Yuswen, Dedi (Jurnal Manajemen Teknologi, 2008)
The mechanism of selecting and evaluating exploration prospects for oil and gas exploration drilling projects is usually done individually with considerations on the technical and economical aspects. The technical aspect of the prospect is focused on to how far a chance of oil and gas exists, and this aspect is also referred to as risk aspect of the prospect. On the other side, economic evaluation is done based on predicted resource recovery, an evaluation of the level of prospect using general investment indicators. Technical aspects used to be assessed as a standard procedure in the exploration projects, but economic aspects will still need to be intensively explored. In the condition where the availability of drilling sites are getting scarcer as well as the very limited budget, this research proposes the tools of analyses for optimizing the selection and planning of exploration projects, namely the Discounted Cash Flow and the Decision Tree of Timing Option. Analyses have been conducted in this research, by inputting a three-year REPA(Region Risk Factors) Index. The result from those analyses is an index of investment called the RI3 index. Comparing it with the application of Zero-One Programming method in portfolio analyses, it was shown that the ranks of investment from both analyses are different.Â Keywords:Â investment portfolio, risk factors, risk assessment, discounted cash flow, decision tree of timing option